FEATURES OF ROMANESQUE STYLE INTERIORS - Sidorova, Olena; Bozhko, Mariia (Theory and practice of design, 2025)
The article analyzes the interior space of Romanesque architectural structures as a reflection of the spiritual, aesthetic, and functional principles of the medieval era. Particular attention is paid to the techniques of forming an interior in the Romanesque style using compositional and coloristic means, traditional and modern materials, as well as a certain semantic series and the possibilities of implementing the identified arsenal of techniques and means in modern design. The purpose of the study: analysis of the features of the Romanesque style in the interior, identification of style-forming elements, determination of the color palette, their symbolism and role in the formation of the spatial environment. Methodology: To achieve the goal, a comprehensive interdisciplinary approach was used, encompassing methods of historical and cultural, art history, and architectural analysis. Comparative analysis was used to study the features of Romanesque interiors in relation to other architectural styles. Results. The study provides an understanding of some key features and principles of organization of residential and sacred interiors of several typical structures that have survived to the present day or have been reconstructed based on historical data. Aspects of spatial organization, materials, and interior decor are considered. Scientific novelty. The principles of organizing internal space in the Romanesque era depended on the characteristics of historical development, social and religious traditions, geographical location, and available building materials in different regions of Europe. The style-forming elements were arches, vaults, exposed stonework of walls and exposed wooden ceiling beams, plot compositions of column capitals and ornaments that carried a certain symbolic meaning, especially in sacred buildings, emphasizing the spiritual essence of the space. The main accent of the interior was a fireplace with knightly attributes. Practical relevance. Understanding the fundamental principles of Romanesque aesthetics and its functional basis will allow for a more conscious use of the principles of spatial organization characteristic of this era (clear zoning, axial and centric organization of compositions).